How do research institutes learn? - Jochen Gläser (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 1997)
The aim of this paper is to contribute to the theory of organisational learning (OL) by developing a middle range theory of how research institutes learn. Because of a research institute's specific division of labour in the organisation-environment interactions, the means of mediation between individual and organisational learning are of particular interest. To study these means, a secondary analysis of interviews with scientists of four newly founded East German research institutes was carried out. The early development of these institutes was determined by the necessity to learn as fast as possible in order to achieve quick integration into the German research landscape. The results of the empirical analysis show (1) the importance of `unconventional' OL by hiring West German scientists who are experienced in the relevant contexts in which the institute has to operate; (2) the close connection between the modes of `loose coupling', on the one hand, and, on the other hand, the mediation between individual learning and OL; and (3) the need to enrich analyses of research institutes by introducing a variable describing the fragmentation of an institute's technical core, thus going beyond the classical variables for describing organisations' technologies (task uncertainty and complexity). – – Mit diesem Papier soll zu einer Theorie mittlerer Reichweite über das Organisationslernen (OL) von Forschungsinstituten beigetragen werden. Die in Forschungsinstituten auftretende besondere Arbeitsteilung in den Interaktionen der Organisation mit ihrer Umwelt läßt die Frage nach der Art und Weise der Vermittlung zwischen Individual- und Organisationslernen besonders interessant erscheinen. Diese Vermittlungsprozesse wurden in einer Sekundäranalyse von Interviews mit Wissenschaftlern aus vier neugegründeten ostdeutschen Forschungsinstituten untersucht. Um sich in die deutsche Wissenschaftslandschaft integrieren zu können, mußten diese Institute in ihrer ersten Entwicklungsphase so rasch wie möglich lernen. Die Ergebnisse der empirischen Untersuchung zeigen (1) die Bedeutung des `unkonventionellen' OL durch die Einstellung westdeutscher Wissenschaftler, die das notwendige Wissen über wichtige Umwelten haben, (2) den Zusammenhang zwischen den in Forschungsinstituten auftretenden Varianten einer losen Kopplung einerseits und der Vermittlung zwischen Individual- und Organisationslernen andererseits sowie (3) die Notwendigkeit, bei der Analyse von Forschungsinstituten die klassischen Variablen zur Beschreibung der Technologie (Aufgabenunsicherheit und Komplexität) durch eine Variable zu ergänzen, die die Fragmentierung des technologischen Kerns eines Forschungsinstitutes beschreibt.
Keywords: 300; Forschungsinstitut; Unternehmensorganisation; Lernprozess; Neue Bundesländer; Theorie